Ventilator-Associated Lung Injury during Assisted Mechanical Ventilation - Saddy, Felipe; Sutherasan, Yuda; Rocco, Patricia R. M.; Pelosi, Paolo (Seminars in Respiratory and Critical Care Medicine, 2014)
Assisted mechanical ventilation (MV) may be a favorable alternative to controlled MV at the early phase of acute respiratory distress syndrome (ARDS), since it requires less sedation, no paralysis and is associated with less hemodynamic deterioration, better distal organ perfusion, and lung protection, thus reducing the risk of ventilator-associated lung injury (VALI). In the present review, we discuss VALI in relation to assisted MV strategies, such as volume assist–control ventilation, pressure assist–control ventilation, pressure support ventilation (PSV), airway pressure release ventilation (APRV), APRV with PSV, proportional assist ventilation (PAV), noisy ventilation, and neurally adjusted ventilatory assistance (NAVA). In summary, we suggest that assisted MV can be used in ARDS patients in the following situations: (1) Pao2/Fio2 >150 mm Hg and positive end-expiratory pressure ≥ 5 cm H2O and (2) with modalities of pressure-targeted and time-cycled breaths including more or less spontaneous or supported breaths (A-PCV [assisted pressure-controlled ventilation] or APRV). Furthermore, during assisted MV, the following parameters should be monitored: inspiratory drive, transpulmonary pressure, and tidal volume (6 mL/kg). Further studies are required to determine the impact of novel modalities of assisted ventilation such as PAV, noisy pressure support, and NAVA on VALI.
Keywords: acute respiratory distress syndrome; assisted mechanical ventilation; ventilator-associated lung injury; transpulmonary pressure